Youth Training Programs Beyond Employment. Experimental Evidence from Argentina - María Laura Alzúa; Guillermo Cruces; Carolina Lopez (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2015)
Youth training programs and their evaluations are ubiquitous, yet there is relatively little evidence on the mechanisms through which they operate and their effect on outcomes beyond the labor market. This is the motivation of our study of entra21 , a job training program for low income youth in Cordoba, Argentina. The program included life-skills and vocational training, as well as internships with private sector employers. Participants were allocated by means of a public lottery. We rely on detailed monthly administrative records for program participants, from which we construct a panel dataset including formal employment status, employment spells, earnings and welfare participation. These administrative records allow us to establish the effects of the program in the short term (18 months), but also – exceptionally for programs of this type in Latin America – in the medium term (36 months). The results indicate sizable gains of about 8 percentage points in formal employment in the short term (about 32% higher than the control group), although these effects tend to dissipate in the medium term. Contrary to what has been found for similar programs in the region, the effects of entra21 are substantially stronger for men, for whom the effects persist in the medium run. A dynamic analysis of employment transitions indicates that the program operates through an increase in the persistence of formal employment rather than from more frequent entries into employment. Program participants also exhibit earnings up to 50% higher than those in the control group, and an analysis of bounds indicates that these gains result from both higher employment levels and higher wages. The higher persistence and higher earnings suggest that the program was successful in increasing the human capital of participants rather than (or in addition to) providing contacts or formal intermediation. With respect to results beyond employment, women selected for the program exhibit lower levels of welfare dependency – younger participants (aged 18 to 24) are less likely to receive child-related public cash transfers over the whole period of analysis. Finally, we present original evidence on the relationship between formal employment and consumer credit use. Program participants exhibit a higher probability of having requested consumer credit, and a higher probability of holding bank debts in good standing. These results indicate that training and internship programs directed at disadvantaged youth can provide other indirect benefits that are not usually accounted for in existing evaluations.
Keywords: J08; J24; J68; O15; 330; youth labor training programs; youth unemployment; field experiment; Junge Erwachsene; Niedrigeinkommen; Arbeitsmarktintegration; Jugendarbeitslosigkeit; Cordoba (Argentinien; Provinz); Argentinien